Pola Pemberitaan CNN, MetroTV, dan TVRI: Analisis Konten dan Perbandingan Media - Nurulhuda, Nada Syifa; Pramudya, Aissyah Lintang; Amalia, Selma Dwi; Ritonga, Putra Hamonangan; Syaharani, Zevanya Praja; Narindra, Rochella Amalia; Wicaksana, Dika Hikmah; Widiastiwi, Alisha Reva; Camilla, Garneta Rizka; Sachmaso, Hana Humaira; Putri, Cinta Aisyah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The mass media has a central role in shaping public opinion through agenda setting and framing mechanisms. This study aims to analyze the news reporting patterns applied by CNN Indonesia, MetroTV, and TVRI with a focus on the aspects of factuality, actuality, and accuracy. Through a content analysis approach, this study compares how the three media present certain issues and how the differences in these approaches have implications for public perception of an event. The results of the study show that each media has different news presentation characteristics: CNN Indonesia prioritizes speed and data visualization, MetroTV tends to be analytical with political nuances, while TVRI emphasizes an educational approach and neutrality. These differences reflect variations in framing information that have the potential to influence public opinion differently. This study is expected to contribute to strengthening media literacy and increasing public awareness of the importance of journalistic integrity in conveying information.